Defaunation and changes in climate and fire frequency have synergistic effects on aboveground biomass loss in the brazilian savanna - Maciel, Everton A.; Martins, Valeria F.; de Paula, Mateus D.; Huth, Andreas; Guilherme, Frederico A.G.; Fischer, Rico; Giles, André; Barbosa, Reinaldo I.; Cavassan, Osmar [UNESP]; Martins, Fernando R. (Elsevier, 2021)
As a result of anthropogenic pressure, three drives are expected to affect Brazilian savannas: an increase in the dry season, more frequent fire events, and defaunation. These drivers are a trigger for biodiversity loss and undermine the ecosystems services like carbon storage. Here our goal was to analyze how these drivers can affect the structure and dynamics of the savanna's tree species and how they impact the savanna's total estimating aboveground biomass (AGB). We analysed eight sites that comprise a physiognomic gradient from open savanna to savanna woodland. The species were classified by three traits: phenological strategies (deciduous or evergreen), fire resistance (resprouting or non-resprouting), and dispersal syndrome (animal or non-animal). Then, we modelled AGB loss in a dry season in the austral winter, a 2 °C increase in daily temperature, five fire events by decadal-series, and a defaunation scenario. Although climate change, change in fire frequency, and defaunation effects impact AGB separately, they also have a synergistic effect. This effect was observed in functional strategies and also in the total AGB of the community. In some cases, the total AGB loss exceeded 70%. The negative effects on performance were highest in species which were decidual, non-resprouting, and which employed animal dispersal for their seed. If different types of disturbances are not controlled in the near future, savanna communities will be dominated by evergreen, resprouters, and non-animal dispersed species, representing a steeply decline in the diversity of species and ecosystem functions.
Keywords: Biodiversity loss; Biodiversity management; Carbon balance; Cerrado; Disturbance; Forest simulations